Diagnostic performance of angiography-based fractional flow reserve by patient and lesion characteristics - Kobayashi, Yuhei; Collet, Carlos; Achenbach, Stephan; Engstrom, Thomas; Assali, Abid; Shlofmitz, Richard A.; Fournier, Stephane; Kirtane, Ajay J.; Ali, Ziad A.; Kornowski, Ran; Leon, Martin B.; De Bruyne, Bernard; et al. (EuroIntervention, 2021)
Background: A large, prospective, multicentre trial recently showed that fractional flow reserve (FFR) derived from coronary angiography (FFRangio) has an accuracy of 92% compared with conventional guide-wire-based FFR (FFRwire); however, little is known about whether specific patient/lesion characteristics affect the diagnostic performance.
CRIS-Team WoS Importer:2021-08-06